Visual Attention in West Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The maturation of visual attention is evaluated prospectively in a study of infants with West syndrome (WS) before, during and after the onset of seizures, followed until age 24 +/- 2 months at Catholic University, Rome, and University of Pisa, Italy.